Results of the Rural Investment Climate Assessment (RICA) in Indonesia : Final Report - World Bank (Washington, DC, 2012)
The Rural Investment Climate Survey (RICS) carried out in 2006 sampled more than 2,500 predominantly very small firms in six rural districts in Indonesia [Labuhan Batu (North Sumatra), Kutai (East Kalimantan), Barru (South Sulawesi), Malang Java), Badung (Bali), Sumbawa (NTB)]. It compiled information on labor force, credit, infrastructure, marketing and competition, the diffusion of technical knowledge, local governance and the main obstacles that firms face. The Indonesian RICS is an in-depth, quantitative survey of 2549 non-farm enterprises, 2782 households and 149 communities in 6 rural districts (Kabupaten). The survey was conducted in January/February 2006 and comprised a linked survey of non-farm enterprises and households. Non-farm enterprises are defined as all enterprises except those undertaking primary agriculture, forestry and fishery activities, although firms which undertake the processing and trading of primary commodities were included. The survey includes both formal and informa businesses and examines both rural and urban areas of rural districts to generate comparative data. The key findings are: a) there is a strong rural-urban divide in educational attainment of workers and huge differences between districts with Malang being particularly disadvantaged. Workers in household enterprises, the production sector and part-time workers are significantly undereducated; and b) tax payments are highly skewed: only medium and large firms pay a large share of their taxes to the central government, whereas for small and micro-enterprises the motor vehicle tax and levies from village and sub-district officials' playa large role. All of the payments have a highly skewed distribution with many firms (43 percent) paying no levies and fees at all.